Safety and efficacy of video assisted thoracoscopic surgery for non-malignant pathologies: a prospective observational study - Gajbhiye, Raj N.; Tirpude, Bhupesh Harish; Dhahiya, Akshay; Akulwar, Vikrant; Bhanarkar, Hemant; Deshpande, Gayatri; Jhahagirdar, Deepa; Kodape, Girish (International Surgery Journal, 2021)
Background: Video-assisted thoracic surgery (VATS) had been widely accepted because of its low complication rate, tolerable postoperative pain and early recovery of pulmonary function. Hence the present study was undertaken to assess safety and efficacy of VATS and also analyze the surgical outcomes of VATS procedures for non-malignant thoracic pathologies. Methods: A total of 32 patients with non-malignant pathologies of thorax to undergo VATS lobectomy and thoracotomy conversion cases initially approached by VATS lobectomy were enrolled. Demographic data and surgical information were noted and compare between infection and non-infection group. Primary outcomes were thoracotomy conversion rate, period of thoracic drainage, length of hospital stay, and complications. Results: The majority of patients were in the age group of 36-45 years (28.12%) with female predominance (62.50%). The commonest clinical presentation was hydropneumothorax (28.12%). Most common infective and non-infective aetiology was lung hydatid (28.12%) and benign nodule (18.75%) respectively. The commonest surgical procedures conducted using VATS were lobectomy (34.37%), and decortication (25%). The mean blood loss among the cases was 315.9±36.46 ml. Mean operative time was 157.18±12.37 minutes. Among 6.25% cases thoracotomy was conducted in view of difficult hilar dissection, while among 3.12% cases each of indistinct anatomy and bleeding. Mean duration of thoracic drainage was 6.78±1.69 days and mean hospital stay was 8.2±3.2 days. 6.25% cases had fatal complications while 21.87% cases had milder complications. Only one case recurred while 96.87% cases cured. Conclusions: VATS lobectomy for benign disease is feasible and effective in selected cases, regardless of the presence of infection.